The City :A Novel - Koontz, Dean R 1945- (Dean Ray) (New York : Bantam Books, 2014)
"#1 New York Times bestselling author Dean Koontz is at the peak of his acclaimed powers with this major new novel. The city changed my life and showed me that the world is deeply mysterious. I need to tell you about her and some terrible things and wonderful things and amazing things that happened. and how I am still haunted by them. Including one night when I died and woke and lived again. Here is the riveting, soul-stirring story of Jonah Kirk, son of an exceptional singer, grandson of a formidable "piano man," a musical prodigy beginning to explore his own gifts when he crosses a group of extremely dangerous people, with shattering consequences. Set in a more innocent time not so long ago, The City encompasses a lifetime but unfolds over three extraordinary, heart-racing years of tribulation and triumph, in which Jonah first grasps the electrifying power of music and art, of enduring friendship, of everyday heroes. The unforgettable saga of a young man coming of age within a remarkable family, and a shimmering portrait of the world that shaped him, The City is a novel that speaks to everyone, a dazzling realization of the evergreen dreams we all share. Brilliantly illumined by magic dark and light, it's a place where enchantment and malice entwine, courage and honor are found in the most unexpected quarters, and the way forward lies buried deep inside the heart. Acclaim for Dean Koontz "A rarity among bestselling writers, Koontz continues to pursue new ways of telling stories, never content with repeating himself."--Chicago Sun-Times "Tumbling, hallucinogenic prose. 'Serious' writers. might do well to examine his technique."--The New York Times Book Review "[Koontz] has always had near-Dickensian powers of description, and an ability to yank us from one page to the next that few novelists can match."--Los Angeles Times "Koontz is a superb plotter and wordsmith. He chronicles the hopes and fears of our time in broad strokes and fine detail, using popular fiction to explore the human condition."--USA Today "Characters and the search for meaning, exquisitely crafted, are the soul of [Koontz's] work. One of the master storytellers of this or any age."--The Tampa Tribune "A literary juggler."--The Times (London)"--
"There are millions of stories in the city--some magical, some tragic, others terror-filled or triumphant. Jonah Kirk's story is all of those things as he draws readers into his life in the city as a young boy, introducing his indomitable grandfather, also a "piano man;" his single mother, a struggling singer; and the heroes, villains, and everyday saints and sinners who make up the fabric of the metropolis in which they live--and who will change the course of Jonah's life forever. Welcome to The City, a place of evergreen dreams where enchantment and malice entwine, where courage and honor are found in the most unexpected corners and the way forward lies buried deep inside the heart"--
Library Journal Prepub Alert
Adult.
Adult.
Keywords: Musicians -- Fiction; City and town life -- Fiction; Fantasy fiction; Adventure fiction; Love stories